The rescue of Jerusalem: a view from the Nile Valley - Dodson, Aidan (The journal of Hebrew scriptures, 2019)
This volume focuses on Henry Aubin's thesis in The Rescue of Jerusalem: The Alliance between Hebrews and Africans in 701 BC (2002) that an army of Egypt's Kushite Dynasty (also known as the Twenty-fifth Dynasty) was influential in saving Jerusalem from capture by Assyrian forces. Eight scholars from a range of disciplines—biblical studies, Assyriology, Egyptology and Nubiology—assess the thesis and explore related ideas. Most of the evaluators tilt in varying degrees toward the plausibility of the book's thesis. The volume concludes with Mr. Aubin's response to each essay.